Anthelmintic and analgesic activities of different solvent fractions of crude methanolic extract of Baccaurea ramiflora (Lour.) fruit peels and seeds with molecular docking analysis - Mantasha Tabassum; Najneen Ahmed; Joynta Majumder; Nazifa Tabassum; Md. Ashraful Islam (Shahrekord University of Medical Sciences, 2024)
Introduction: Baccaurea ramiflora Lour, locally known as Latkan, is a popular fruit in Bangladesh used for its anthelmintic and analgesic activities. This study aimed to compare the anthelmintic and analgesic activities of different solvent fractions of crude extract from B. ramiflora fruit seed and peel. Methods: Cold extraction followed by the Kupchan scheme was employed to obtain various solvent fractions. In vivo anthelmintic activity was assessed using Pheretima posthuman, while analgesic activity was evaluated via writhing and tail immersion tests on Swiss albino mice. Molecular docking studies of four reported phytochemicals from B. ramiflora on analgesic and anti-parasitic protein targets were conducted using the PyRx. Results: Results revealed significant anthelmintic activity in seed petroleum ether, chloroform, ethyl acetate, and acetone solvent fractions in a dose-dependent manner, with acetone extract exhibiting the highest activity. Writhing was significantly reduced in all seed and peel extracts, with the highest inhibition observed at 200 mg/kg dose. Moreover, seed chloroform and peel ethyl acetate extracts displayed the longest pain reaction times in the tail immersion model (6.924 ± 0.264 seconds and 6.562 ± 0.157 seconds, respectively). Molecular docking revealed strong binding interactions of Baccariminose C and D (≥8.2 kcal/mol) with all studied protein targets. Conclusion: This study confirms the anthelmintic and analgesic activities of B. ramiflora fruit peel and seed extracts. These results contribute to the understanding of the medicinal properties of B. ramiflora and its potential applications in pharmaceuticals.